I'm pretty sure that it would be 1,000...
Answer:
(2, 3 )
Step-by-step explanation:
Given the 2 equations
3x - 5y = - 9 → (1)
x + 2y = 8 → (2)
Multiplying (2) by - 3 and adding to (1) will eliminate the x- term, that is
- 3x - 6y = - 24 → (3)
Add (1) and (3) term by term to eliminate x
(3x - 3x) + (- 5y - 6y) = (- 9 - 24), that is
- 11y = - 33 ( divide both sides by - 11 )
y = 3
Substitute y = 3 into either of the 2 equations and solve for x
Substituting in (2)
x + 2(3) = 8
x + 6 = 8 ( subtract 6 from both sides )
x = 2
Solution is (2, 3 )
Answer:
x8+12
x+1
Step-by-step explanation:
Suppose :
2^x = t ..**&**.. 3^y = u
_____________________________
t + u = 9 × 3 3t + 3u = 27
=====》
2t - 3u = 8 2t - 3u = 8
+ __________
5t = 35
5 × t = 5 × 7
t = 7
&
u = 2
________________________________
Thus :
2^x = 7 ===》 x = Log _ 2 { 7 }
3^y = 2 ===》 y = Log _ 3 { 2 }
First we will change them on the same denominator which will be 12. If we do something to the denominator we must do the same to the numerator so :
For 1/3 we get 4/12 because (1/3)*4 = 4/12
And for 2/3 we get 8/12 because (2/3)*4 = 8/12
So 1/3 is the smaller fraction, 7/12 is in the middle and 2/3 is the bigger fraction.